LATE WEANING: THE MOST SIGNIFICANT RISK FACTOR IN THE DEVELOPMENT OF IRON DEFICIENCY ANAEMIA AT 1-2 YEARS OF AGE - Ali, Sultan N; Zuberi, RW (Journal of Ayub Medical College Abbottabad, 2003)
Background: The global prevalence of iron deficiency anaemia in young children is quite high and children between the ages of 1-2 years are at maximum risk. The complications of anaemia are well known, and side effects may go unnoticed and may have an adverse effect on child’s life. Therefore, prevention of anaemia becomes enormously important, and the need to look for parameters and predisposing factors that may lead to iron deficiency anaemia in small children is imperative. This study was designed to determine the association of iron deficiency anaemia with late weaning in 1-2 years of children. Method: A case control study was conducted from July 1993-July 1995, at the Community Health Centre (CHC), of the Aga Khan University Hospital, at Karachi, Pakistan. The study included 50 cases and 100 controls. A questionnaire was filled by mothers after taking consent. Data was analyzed by chi-square, t-tests, bivariate analysis and multiple logistic regression. Results: Through bivariate analyses, late weaning, family income, mother’s education, the numbers of pregnancies, live births and living children, were found to be statistically significant. These variables were run through a multiple logistic regression model and late weaning was found to be the most significant. 60% of cases and 9% of controls were weaned late (p<0.001). The mean age of weaning was 7.04 months among cases and 4.46 months among controls (p<0.001). Conclusion: Among all the variables studied, late weaning was the most important predictor of iron deficiency anaemia in 1-2 years of age. KEY WORDS: Anaemia, iron deficiency; weaning; feeding methods; feeding behaviour.